2020
DOI: 10.3311/ppci.15966
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Octagonal Hooked Collar Countermeasure to Reduce Scour Around a Single Bridge Pier

Abstract: Pier modification countermeasures are essential as they play a vital role in protecting pier against local scour action. Current study investigates experimentally the scour around vertical pier of octagonal cross section with pier modification such as newly proposed octagonal hooked collar is explored, in steady uniform state, under clear water condition. The results of pier scour without any modification were used as a reference to compute the efficiency of hooked collar provision around octagonal pier. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Hence, a range of combinations with four different widths (H w = 1.5W p , 2W p , 2.5W p , 3W p cm) and three sidewall heights (H wh = 0.15W p , 0.3W p , 0.45W p cm) is examined. The hooked collar thickness is adjusted as 5 mm [28]. Whilst the ratio of flume breadth 'B' to width of pier, B/W p is 20, at the contracted cross section no bed degradation is noticed; this agrees well with [37] that reported that contraction scouring effect becomes minimum when B/W p > 10.…”
Section: Hooked Collar Countermeasuresupporting
confidence: 76%
See 4 more Smart Citations
“…Hence, a range of combinations with four different widths (H w = 1.5W p , 2W p , 2.5W p , 3W p cm) and three sidewall heights (H wh = 0.15W p , 0.3W p , 0.45W p cm) is examined. The hooked collar thickness is adjusted as 5 mm [28]. Whilst the ratio of flume breadth 'B' to width of pier, B/W p is 20, at the contracted cross section no bed degradation is noticed; this agrees well with [37] that reported that contraction scouring effect becomes minimum when B/W p > 10.…”
Section: Hooked Collar Countermeasuresupporting
confidence: 76%
“…4. The scouring hole depth gradually progresses for the pier without any protection and approaches to a maximal depth and then asymptotically reaches a normal state as reported by [28]. Thus, it may also be mentioned that the rise in the depth of scour decreases temporally.…”
Section: Scouring Depth Developmentmentioning
confidence: 57%
See 3 more Smart Citations